2020
DOI: 10.3390/antiox9121271
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p300 by Garcinol Protects against Cisplatin-Induced Acute Kidney Injury through Suppression of Oxidative Stress, Inflammation, and Tubular Cell Death in Mice

Abstract: Emerging evidence suggests that epigenetic mechanisms such as histone modification are crucially involved in the pathophysiology of acute kidney injury (AKI). The histone acetyltransferase p300 regulates several biological processes through the acetylation of histones or transcription factors. However, the role of p300 in cisplatin-induced AKI remains poorly understood. Therefore, we investigated the effects of garcinol, a potent p300 inhibitor, on cisplatin-induced AKI and explored the mechanisms. Administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 64 publications
2
23
0
Order By: Relevance
“…We demonstrate by ChIP that FOXC2 binds to its promoter and its binding affinity is enhanced by LPS treatment. Our data also reveal that garcinol, a HAT inhibitor, that is specific to p300 and PCAF (Balasubramanyam et al, 2004;Kim et al, 2020;Wang et al, 2020;Kopytko et al, 2021), represses LPS-stimulated histone acetylation at FOXC2 promoter, FOXC2 binding affinity and FOXC2 expression in HPMEC-Im. Our data shows that LPS-stimulated FOXC2 expression in primary HPMEC is also repressed by garcinol consistent with our data in immortalized HPMEC.…”
Section: Discussionsupporting
confidence: 60%
“…We demonstrate by ChIP that FOXC2 binds to its promoter and its binding affinity is enhanced by LPS treatment. Our data also reveal that garcinol, a HAT inhibitor, that is specific to p300 and PCAF (Balasubramanyam et al, 2004;Kim et al, 2020;Wang et al, 2020;Kopytko et al, 2021), represses LPS-stimulated histone acetylation at FOXC2 promoter, FOXC2 binding affinity and FOXC2 expression in HPMEC-Im. Our data shows that LPS-stimulated FOXC2 expression in primary HPMEC is also repressed by garcinol consistent with our data in immortalized HPMEC.…”
Section: Discussionsupporting
confidence: 60%
“…Immunohistochemical staining for 4-hydroxynonenal (4-HNE)—a major product of lipid peroxidation [ 18 ]—revealed that the percentage of the 4-HNE-stained area was increased after DDC feeding ( Figure 2 C,D). Hepatic levels of malondialdehyde (MDA)—another marker of lipid peroxidation [ 19 ]—were also increased ( Figure 2 E). However, the DDC-diet-induced oxidative stress was significantly suppressed by CoPP ( Figure 2 A–E).…”
Section: Resultsmentioning
confidence: 99%
“…The targets are mainly associated with oxidative stress, apoptosis, inflammation, and cell proliferation. According to quantities of studies, apoptosis induced by TNF- α , p53, and caspase-3 [ 43 , 44 ] and inflammation induced by IL-6, TNF- α , and interleukin-1 beta (IL-1 β ) played an essential role in cisplatin-induced kidney damage [ 45 , 46 ]. It was reported that cisplatin increased the expression of proinflammatory cytokine TNF- α , which induced an exogenous apoptotic pathway through its tumor necrosis factor receptor 1 (TNFR1) [ 47 ], and TNF- α can activate proinflammatory cytokines and chemokines such as NF- κ B and trigger oxidative stress, which ultimately aggravates kidney damage [ 48 ].…”
Section: Discussionmentioning
confidence: 99%